CLASSIFYING LEGAL CONCEPTS - KASIMOV Timur Salavatovich; KASIMOVA Dilyara Faritovna; ASYLBAEVA Polina Anatolyevna (Правовое государство: теория и практика)
Classification is a central methodological tool of scientific cognition; it allows to ensure objectivity and minimise subjective factors in scientific research. The purpose of the article is to study and systematise legal concepts, to identify their classification characteristics. The authors endeavour to create a scientifically sound classification that would facilitate the accurate structuring of legal concepts and their adaptation to different spheres of public administration and socio-economic planning. Methods: formallogical (used for a detailed description, consistent generalisation, comprehensive classification and systematisation of information, which is the key stage of this study), theoretical abstraction (reveals the essential concept of classification as a fundamental scientific phenomenon), analysis and synthesis (contribute to the creation of a multilevel classification of legal concepts and in-depth understanding of their theoretical significance, and ultimately – to the formation of a holistic view of the category under study). Results: the article proposes several criteria for classifying concepts, each of which is systematically described with regard to the specifics of its application. The article analyses legal concepts according to a number of criteria: validity, legal force, territorial scope of application and sectoral affiliation, the application of which substantiates the importance of adapting legal concepts to the conditions of territories, including special geopolitical and social conditions, which enables effective management and integration of concepts into the system of strategic planning. The authors emphasise that legal concepts are often integrated into complex documents – strategies and state programmes, thus strengthening their role in the public administration system. The identified differences between short-term and long-term concepts, as well as the significance of their territorial and sectoral adaptation, confirm the appropriateness of the proposed classification.